Gospodarski razvoj hrvatskih zemalja u ranom novom vijeku - osnovne razvojne smjernice - Grgin, Borislav (Array, 2004)
Gospodarski razvoj hrvatskih zemalja u ranom novom vijeku - osnovne razvojne smjernice